Social Activity of Man in Pre-Class Society - Gendrolis, Edmundas (Problemos, 1982)
Basing on a study of ethnographic materials as well as on a critical analysis of two opposed conclusions (the first one admitting the freedom for man of pre-class society quite inconceivable in any other kind of society, while the second one denying any slightest possibility of manifesting human individuality) the author comes to the conclusion: it is society that has always been the real subject of history. It is impossible, however, to ignore the role of individuals in pre-class society along its development. Admitting but limited potentialities of society and man, due to the level of productive forces, the dependence of an individual on a collective body (such dependence has always existed, it is but its character that changes), it is impossible to ignore either certain independence of Man or his initiative, or the changing of traditions.